Дослідження укріплень городища Литовеж на Волині - Петраускас, А.В.; Панишко, С.Д.; Лошик, Д.С.; Чорний, І.О.; Кукса, А.О. (Археологія і давня історія України, 2020)
У статті подаються результати археологічних досліджень городища у с. Литовеж Іваничівського району Волинської області. Встановлено, що на дослідженій ділянці зовнішній вал укріплень городища був споруджений у пізньосередньовічний час, вірогідно, у XVI ст., на ділянці, яка до цього була слабозаселеною. Однак, характер знахідок, близьке розміщення до церкви Св. Параскеви П’ятниці, та, вірогідно, міських воріт, свідчать про інтенсивне використання цієї території у подальшому. Currently, the complex of the hill-fort by the meandering bend of the Bug River channel is divided into two parts: the western one where the castle is located, and the eastern one where the city is obviously placed. During the exploration the rampart of the eastern part of the fortified complex was cut by the trench. The body of rampart is stand on the ancient original surface which looked like a humus substance. It consisted of three consecutive fillings. The first is gray soil up to 0.2 m thick, the second is white sand up to 0.8 m thick, and the third, most high (up to 1.4 m) is the yellow sand that covered the previous one from inside of the rampart. The yellow sand was cut through by well visible pit at the bottom of which the bones, probably human skulls have been found. These filings contained several fragments of pots of the fourteenth and fifteenth centuries.